Global strategies for combating dengue Virus: a review on the control methods - Montasir, Fahim (Brac University, 2024)
A thesis submitted to the Department of Mathematics And Natural Science in partial fulfillment of the requirements for the degree of B.Sc. in Microbiology, 2024.